ABOUT SOME METHODOLOGICAL ASPECTS OF MODELING OF INNOVATIVE TRANSFORMATION OF SOCIAL AND ECONOMIC SYSTEMS - M. K. Dudin; N. V. Lyasnikov (Модернизация, инновация, развитие, 2015)
In article separate methodical basics of modeling of innovative transformation of social and economic systems are covered. Modeling is considered in process aspect taking into account use of special predictive procedures and data-logical models for definition of the directions and specifics of movement of technologies, and also the directions of scientific and technical and technological development, as main conditions of innovative transformation of social and economic systems.